Penerapan Metode Yanbu’a dalam Meningkatkan Cara Cepat Membaca Al-Qur’an Santri di Pondok Pesantren Arridho Depok - Moh.Romli; Zulkarnaen, Andi Achmad; Siti Aminah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study discusses related to the application of the method yanbu`a in improving how to quickly read the Qur’an in the environment of novice students at the Arridho Islamic Boarding School, Depok, who are considered relatively poor at reading. With this background, the researcher was interested in knowing how technically the yanbu'a method was applied at the Arridho Islamic boarding school, Depok. This type of research is descriptive qualitative. Data collection techniques were carried out by interviews and documentation. The data analysis used follows the analysis of the Miles and Huberman models, namely data reduction, data presentation and verification. The results of this study found that; Application of the method yanbu`a in improving how to quickly read the Qur'an in the novice student environment at the Arridho Islamic Boarding School in Depok, it is carried out with several methods based on active, innovative, creative, effective and fun learning, time discipline and patience following the stages of learning the Qur'an Methods yanbu`a, such as al-Quran encouragement with senior santri before Musyafahah with the teacher, istiqomah in murojah or repeating the reading, letter makhrijul practice, al-Fatihah, At-tahiyat and Juz `Amma reading practice, so based on the research results, that the yanbua' method is one of the keys to the students' success in reciting the al-Quran well in accordance with tajwid knowledge.